Peningkatan Kapasitas Petani Kelompok Tani Pelangi melalui Penyuluhan Edukatif dan Praktik Pengelolaan Hama Ramah Lingkungan - Nenotek, Petronella S.; Kadja, Don H.; Ludji, Rika; Simamora, Agnes V.; Hahuly, Mayavira V.; Nahas, Agustina E.; Kasim, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
The main issue faced by Kelompok Tani Pelangi (Pelangi Farmer Group) in lowland rice cultivation is the frequent attack of pests and diseases, such as brown planthopper, rice stem borer, and rice bug. To control these pests, most farmers still rely heavily on synthetic pesticides without considering their impacts on beneficial organisms and the environment. This Community Partnership Programme aims to enhance farmers' capacity in environmentally friendly pest management through educational outreach and field-based practices. The methods employed in this programme include educational sessions, hands-on field demonstrations, interactive discussions, and questionnaire-based evaluations. The material delivered covered the identification of pests and diseases in rice, the introduction and implementation of eco-friendly pest control strategies, correct use of synthetic pesticides, and the role and function of refugia plants in conserving natural enemies. Evaluation results indicated a positive impact on the knowledge of farmer group members: 98% were able to identify pest types and their symptoms, 67% recognised predators in the field, 50% understood the principles of appropriate pesticide use, 60% comprehended the negative impacts of pesticides, and 44% recognised the benefits of refugia plants in the rice agroecosystem. The active participation of farmers during discussions and practical sessions reflects a behavioural shift towards sustainable farming practices. This Community Partnership Programme (PKM) has proven effective in improving ecological awareness and technical skills among members of Kelompok Tani Pelangi and is recommended as a model for empowering farmers in surrounding areas through the Integrated Pest Management (IPM) approach.